2006
DOI: 10.1002/cncr.22224
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of hematuria home screening for bladder cancer in men

Abstract: BACKGROUND.The objectives of this study were to determine whether bladder cancer (BC) screening in healthy men could lead to earlier detection and reduced BC mortality compared with unscreened men and to determine long‐term outcomes of a geographically defined, unscreened population with newly diagnosed BC.METHODS.In 1987 and from 1998 to 1992, 1575 men ages 50 years and older who were solicited from well patient rosters in clinics in and around Madison, Wisconsin, tested their urine repetitively with a chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(99 citation statements)
references
References 73 publications
3
90
3
3
Order By: Relevance
“…75 Repeat home urine dipstick testing followed by medical evaluation of positive patients may achieve 90-95% sensitivity. 76 With the home hematuria testing protocol, newly diagnosed patients with bladder cancer had muscle invasion in only 10% of cases, as opposed to 60% in newly diagnosed bladder cancer patients who had not been screened for hematuria. 76 This translated into lower disease-specific and overall mortality than unscreened patients.…”
Section: Implications For the Detection And Prevention Of Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…75 Repeat home urine dipstick testing followed by medical evaluation of positive patients may achieve 90-95% sensitivity. 76 With the home hematuria testing protocol, newly diagnosed patients with bladder cancer had muscle invasion in only 10% of cases, as opposed to 60% in newly diagnosed bladder cancer patients who had not been screened for hematuria. 76 This translated into lower disease-specific and overall mortality than unscreened patients.…”
Section: Implications For the Detection And Prevention Of Bladder Cancermentioning
confidence: 99%
“…76 With the home hematuria testing protocol, newly diagnosed patients with bladder cancer had muscle invasion in only 10% of cases, as opposed to 60% in newly diagnosed bladder cancer patients who had not been screened for hematuria. 76 This translated into lower disease-specific and overall mortality than unscreened patients. Unfortunately, the positive-predictive value of hematuria is only 0.08%.…”
Section: Implications For the Detection And Prevention Of Bladder Cancermentioning
confidence: 99%
“…Messing et al found that detecting microscopic hematuria by using repetitive home hematuria reagent-strip testing was an effective means of identifying bladder cancer at noninvasive stages and found a decreased mortality rate due to bladder cancer in the screened cohort at 14-year follow-up. 8 On the basis of findings such as these, a randomized, prospective, screening trial is warranted to further explore the role of screening in the detection of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that widespread screening could decrease mortality from the disease. 2 The current standards of care for detecting and monitoring BC are cystoscopy, voided urine cytology and imaging. 3 Given the cost and invasive nature of such diagnostic techniques, looking for sensitive and specific biomarkers, as well as noninvasive early detection tests for BC, becomes an urgent subject.…”
Section: Introductionmentioning
confidence: 99%